The provision and utilization of essential health services in Afghanistan during COVID-19 pandemic - Neyazi, Narges; Lindan, Christina; Perdes, Saber; Ibrahimi, Abdul Ghani; Horemans, Dirk; Al Afsoor, Deena (Frontiers in Public Health, 2023)
The COVID-19 pandemic has disrupted provision of essential health services and overwhelmed even robust health systems worldwide. The Afghanistan health system has suffered both from the pandemic, as well as from political upheaval and regime change. We evaluated essential service delivery using data collected from a cross-sectional survey of health care facilities in Afghanistan based on administration of a World Health Organization standardized assessment of frontline service readiness. Facility managers were asked to report on changes in health care service delivery in late 2021 and early 2022 (corresponding to the end of a significant national COVID-19 surge in infections) compared to the same period one year earlier. Among health facilities evaluated; 29 were in urban and 63 were in rural settings. Most facilities reported an increase in the provision of outpatient care particularly in maternal and child health services as well as for tuberculosis, chronic respiratory diseases, mental health, and substance abuse; the number of in-patients also increased. In contrast, provision of services for malaria, neglected tropical diseases, and community outreach programs decreased. Nearly all facilities used strategies to maintain services, including targeting high-risk patients, promoting self-care, and redirecting patients to alternative health care sites. Nearly ¾ three fourth (70.6%) of facilities provided no training about COVID-19 to staff; only 65.2% referred COVID-19 patients to designated hospitals and 44.6% had safe transportation for these patients. Increased demand for services during this period was likely due to a backlog in need generated during the proceeding COVID-19 surge and the political changes happened a few months earlier to this survey. Facilities used various methods to maintain services, although the decrease in provision of community outreach was concerning. Facilities appeared to be able to maintain essential health services, despite an increase in demand as a result of the pandemic. However, awareness and training of COVID-19 protocols and appropriate and safe referrals need to be improved. In general, these series of surveys are very informative and helpful to identify the gaps and bottlenecks any changes in provision of essential health services and leads can facilitate to recovery of health systems during and after pandemics.